Combined Treatment with Laser Sintering and Zirconium: A Case Report of Dentinogenesis Imperfecta. (6th March 2013) - Ayyildiz, Simel; Sahin, Cem; Akgün, Özlem Marti; Basak, Feridun
Abstract : Osteogenesis imperfecta (OI) is a heterogeneous disorder of connective tissue that manifests mainly as skeletal deformity and bone fragility. Dentinogenesis imperfecta (DI) is sometimes an accompanying symptom of OI. The treatment protocol of these patients varies according to the clinical appearance. The case report here describes complete mouth rehabilitation of an 18-year-old male patient with OI and DI using direct metal laser sintering (DMLS) technique of metal-ceramic restorations and zirconium all-ceramic crowns. DMLS is an additive metal fabrication technology that is simpler, more precise, and healthier than conventional manufacturing and can be remarkably cost effective. Moreover, the technique affords highly accurate production of fixed partial dentures with ideal marginal fit and excellent mechanical properties. The patient was treated using a multidisciplinary strategy that focused on controlling caries, protecting teeth from further wear, obtaining an appropriate vertical dimension, and providing soft tissue support to return the facial profile to a normal appearance using new technology in the field of prosthetics.